Ultrastructural Analysis of Megakaryocytes in GPV Knockout Mice - Poujol, Christel; Ramakrishnan, Vanitha; DeGuzman, Francis; Nurden, Alan T.; Phillips, David R.; Nurden, Paquita (Thrombosis and Haemostasis, 2000)
Lesions in the genes for GPIbα, GPIbβ or GPIX result in a bleeding diathesis, the Bernard-Soulier syndrome (BSS), which associates a platelet adhesion defect with thrombocytopenia, giant platelets and abnormal megakaryocytes (MK). The role of GPV, also absent in BSS, was recently addressed by gene targeting in mice. While a negative modulator function for GPV on thrombin-induced platelet responses was found in one model, the absence of GP V had no effect on GPIb-IX expression or platelet adhesion. Our study extends previous results and reports that electron microscopy of bone marrow from the GPV knockout mice revealed a normal MK ultrastructure and development of the demarcation membrane system (DMS). There was a usual presence of MK fragments in the bone marrow vascular sinus. Immunogold labelling of MK from the knockout mice showed a normal distribution of GPIb-IX in the DMS and on the cell surface. The distribution of fibrinogen, vWF and P-selectin was unchanged with, interestingly, P-selectin also localised within the DMS in both situations. Thus GPV is not crucial to MK development and platelet production, consistent with the fact that no mutation in the GPV gene has as yet been described in BSS.
Keywords: GPV knockout mice; GPIb-IX; megakaryocytes; electron microscopy